Deep desulfurization of real fuel oils over tin-impregnated graphene oxide-hydrogen peroxide and formic acid catalyst-oxidant system. (4th March 2023) - Yaseen, Muhammad; Subhan, Sidra; Khan, Kifayatullah; Farooq, Muhammad Usman; Ahmad, Waqas; Seema, Humaira; Naz, Rafia; Subhan, Fazle
Abstract : Herein, Tin-impregnated graphene oxide (Sn/GO) composite was designed and tested for the catalytic removal of sulfides from the simulated and real commercial oils in the hydrogen peroxide and formic acid (HCOOH/H2 O2 ) oxidation system. The prepared GO and Sn/GO were characterized in terms of surface morphology and other catalytic properties, which confirmed that the Sn/GO catalyst has a large surface area and more surface functional groups than GO. The desulfurization activity of the Sn/GO-HCOOH/H2 O2 system was analyzed for the model dibenzothiophene (DBT) and real commercial oil at different substrate concentrations, time, temperature, pH, and oxidant and catalyst doses. The results showed that the Sn/GO-HCOOH/H2 O2 system removed 97% DBT from the model oil and accumulative sulfur of 90%, 69%, and 61%, respectively, from gasoline, diesel, and kerosene oil employing 0.03 g/10 mL catalyst, 2 mL of H2 O2 /HCOOH in 50 min at 50°C, and pH 3. Sn/GO could be recycled up to five consecutive runs retaining more than 57% efficiency. Due to its environmental greenness, ease of preparation, and cost-effectiveness, this unique catalyst-oxidant system can be envisioned for the oxidation of sulfides from real oils. Research Highlights Pristine and Sn-loaded GO composite were synthesized and characterized. The Sn/GO-HCOOH/H2 O2 system oxidized 97 and 90 % DBT from the model and real oil. O 2− radicals generated due to synergism between Sn/GO and HCOOH/H2 O2 species. The Sn/GO-HCOOH/H2 O2 system remained active for five successive reuses. GRAPHICAL ABSTRACT: UF0001